Case Study: Rapid Training of Community Health Workers Using Enskill® - Johnson, W. Lewis (International Journal of Advanced Corporate Learning (iJAC), 2021)
The COVID-19 pandemic caused many workers to lose their jobs, and also resulted in rapid surges in demand for workers with particular skills. In public health there was suddenly a huge demand for community health workers to conduct contact tracing, vaccination, and community outreach. To address this need, our team undertook the challenge of creating an online course that trains workers for community health work in half the time of typical training programs. It utilizes the Enskill® learning platform, which uses AI technology to create simulated scenarios in which trainees practice skills with avatars acting as simulated patients. Fifty-seven training participants without college degrees were recruited for the program from the Hampton Roads region, in collaboration with the Hampton Roads Workforce Council. The first cohorts of trainees were able to complete the training successfully in just eight weeks, and are now being placed in public health and healthcare positions. The approach also shows promise for upskilling existing employees to address skill gaps. The Enskill training program is a competitor in the XPRIZE Foundation’s Rapid Reskilling competition, to quickly reskill under-resourced workers for the digital revolution.